La convivencia escolar a través de la actividad fisica - Vargas Vargas, Camilo Arturo (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The present research focuses on the analysis of physical activity for coexistence improvement in seventh grade students of a private school in Tunja - Boyacá. Con- sequently, we took into account two inductive categories of study: school coexisten- ce and physical activity, for this, we made a diagnosis, through of questionnaire of school coexistence according to Del Rey, Casas and Ortega (2003). Followed by a physical activity program, in which we work and evaluated its result. For this, we used mixed research approach, in which we used action research. In this way, we conclu- ded physical activity, in addition to having a great educational value, it constitutes a spontaneous life action, from which social norms and relationships are fostered.